Friendship, Difference and Education: reflections from Zygmunt Bauman - Rafael Bianchi Silva (Universidade Federal do Rio Grande do Sul, 2018)
The objective of this study is to think about the possible places of friendship from a systematic study on the works of Zygmunt Bauman. Taking as the starting point our living in a time in which human relations are governed by the logic of consumption, the bonds are weakened, leaving the experience of difference in the background. Through the question of love, we understand that friendship can establish new bonds, giving them density. By being based on reciprocity, responsibility and solidarity, the school environment can be a space in which differences can be experienced and a form of resistance to the homogeneity principle can be practiced in contemporary society.